Effect of sugar transporter on galactose utilization in Streptococcus thermophilus - Zhao, Jiancun; Liang, Yan; Zhang, Susu; Xu, Zhenshang (Frontiers in Microbiology, 2023)
Streptococcus thermophilus is a traditional starter for dairy products. The lactose rich in milk is the main carbon source for the growth of S. thermophilus. However, the utilization of galactose by S. thermophilus is strain-specific, and many genetic factors can affect the sugar utilization phenotype of S. thermophilus strains. In this study, S. thermophilus A25, which is capable of utilizing lactose and galactose, was used as the starting strain to construct lactose permease-deficient mutant S. thermophilus ΔlacS.Results showed that S. thermophilus ΔlacS lost the ability to utilize lactose and galactose. Subsequently, the complement vectors expressing complete lactose permease of S. thermophilus and its N-terminal 1-486 amino acid residues were constructed and transformed into S. thermophilus ΔlacS, respectively. By measuring the growth of the recombinant strains, it was found that the strain expressing complete lactose permease of S. thermophilus recovered the growth ability in lactose and galactose medium, while the strain expressing N-terminal of lactose permease recovered the growth ability only in lactose medium. Meanwhile, complement vectors expressing lactose permease and galactose/proton symporter of Escherichia coli were also constructed. The results showed that the transformation of S. thermophilus ΔlacS was not successful with the complement vector expressing E. coli lactose permease, while the strain expressing E. coli galactose/proton symporter could recover its growth ability in the galactose medium. These results suggest that the properties of sugar transporters play an important role in galactose utilization by S. thermophilus.